Structure and thought toward a materialist theory of representational cognition - Sacilotto, Daniel (Diaeresis, 2024)
"This book shows how the different forms of sensory, discursive, and theoretical mediation that characterize human cognition are conducive to a realist epistemological framework that explains how the possibility of knowledge about a mind-independent reality is conceivable"--